Podosphaera xanthii Causing Powdery Mildew on Salvia farinacea in Central China - Liu, Juncong; Wu, Yanpan; Zhang, Wanwan; Fahad, Shah; Qiu, Zongbo; Zhu 朱, Mo 墨 (Plant disease, 2024)
Salvia farinacea, commonly referred as mealycup sage, is a perennial herbaceous plant belonging to the Salvia genus of the Lamiaceae family. It originates from the Mediterranean region, North America, and Europe and is globally cultivated due to its appealing and captivating flowers. Moreover, mealycup sage is utilized as traditional Chinese medicinal plant for treatment of cardiovascular diseases (Li et al. 2018). In October 2023, powdery mildew-like symptoms were observed on Salvia farinacea plants cultivated in a garden located in Xinxiang City, Henan Province, China (113.93, 35.29). The leaves were covered with white and thin masses of mycelia, conidiophores and conidia of the fungus. About 100 plants were checked and 90 % were infected. There were a large number of white colonies with irregular or continuous round lesions on the adaxial and abaxial surfaces of the leaves, covering approximately 80% of the leaf area. The slightly or straight curved conidiophores (n = 30) were 46 to 145× 8 to 11 μm in size and consisted of foot cells, shorter cells and conidia. The ellipsoidal to oval conidia (n = 30), containing fibrosin bodies, were 24 to 35 × 12 to 19 μm in size and had a length/width ratio of 1.8 to 2.1. No chasmothecia were observed on leaves. These morphological features were consistent with those of Podosphaera xanthii (Braun and Cook 2012). Following the previously described method (White et al. 1990; Bradshaw et al. 2022; Zhu et al. 2022a), the sequences of ITS and Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) regions were amplified with specific primers ITS1/ITS4 (ITS1 5'-TCCGTAGGTGAACCTGCGG-3' ; ITS4 5'-TCCTCCGCTTATTGATATGC-3') and PMGAPDH1/PMGAPDH3R (PMGAPDH1 5'-GGAATGGCTATGCGTGTACC-3'; PMGAPDH3R 5'-CCCCATTCGTTGTCGTACCATG-3'), and the resulting sequences were uploaded in GenBank (Accession No. OR761885 and PP236082, respectively). BLASTn analysis showed that the sequence shared 560/565 (99%) and 272/272 (100%) homology with P. xanthii (MW301281) on Impatiens balsamina (Zhu et al. 2022b) and with P. xanthii (ON075658) on Cucumis melo (Bradshaw et al. 2022), respectively. The phylogenetic analysis clearly illustrated that the collected isolate of P. xanthii clustered in the same clade. The pathogenicity was tested according to the method previously described (Zhu et al. 2021). The fungus was inoculated onto the leaf surfaces of three healthy plants by blowing conidia from infected leaves with pressurized air. Non-inoculated plants were treated as control. Both the control and inoculated plants were separately placed in growth chambers under 60% humidity; light/dark, 16 h/8 h; and a temperature of 18°C. After a period of 12-15 days, the leaves of the inoculated plants exhibited signs of powdery mildew, whereas the control group remained unaffected. Therefore, the fungal pathogen was identified and confirmed as P. xanthii (isolate PXSF202310). Previously, P. xanthii was reported on Impatiens balsamina and S. farinacea from China and Korea (Zhu et al. 2021; Choi et al. 2022). As far as we know, this is the first documentation of P. xanthii on S. farinacea in central China. The presence of P. xanthii can lead to a deterioration in plant health and stunted growth, thereby negatively impacting both the decorative and medicinal value of S. farinacea. The recognition of P. xanthii on S. farinacea enhances our comprehension of this pathogen hosts and provides fundamental information for forthcoming disease control studies.